Measuring dynamic and static eco-efficiency in Norwegian dairy farms: a parametric approach - Alem, Habtamu (Frontiers in Environmental Economics, 2023)
Eco-efficiency is gaining popularity to measure the agricultural system's economic and environmental performance. The dynamic eco-efficiency of the agricultural system is assessed in this study using a parametric frontier framework that considers the inter-temporal nature of production decisions and methane emissions. We also estimated the static eco-efficiency model for comparison. The empirical analysis is based on 30 years of unbalanced panel data from 692 dairy farms (1991–2020). The generalized method of moment estimation is used to compute dynamic models. Both dynamic and static models show that dairy farms in the study area used available technology inefficiently, which means that some farmers produced lower outputs per input than the best-performing farmers. According to the dynamic eco-efficiency score, dairy farms only generate 94% of the maximum viable output for the input used. If all dairy farms became eco-efficient, an average dairy farm could raise its output by about 6% using the existing technology. According to the projected scores, farmers might improve their eco-efficiency by 10% on average without using more inputs in a static condition. Policymakers should encourage dairy farms to share information with the best-performing dairy farms on how to improve production while considering environmental concerns.